JavaScript and Open Data - Jeansoulin, Robert (Wiley, 2018)
This book will teach you how to take advantage of the JavaScript language to process data provided on the Internet. Much attention is given to the main JavaScript backbone: prototype based objects, and functional capabilities, while common features (loops, etc.) are summarized in a few cheat-sheets. Only operational features are detailed through the coding of several applications -the second and largest part of the book-, on free-access datasets (e.g. World Bank). It includes: cartography (SVG or API's based), data-sheets access (via Ajax or Jsonp), video data and post-synchronization, and animation examples.